2015
DOI: 10.1039/c5ra11338e
|View full text |Cite
|
Sign up to set email alerts
|

Copper–cobalt synergy in Cu1−xCoxFe2O4spinel ferrite as a highly efficient and regioselective nanocatalyst for the synthesis of 2,4-dinitrotoluene

Abstract: Highly regioselective dinitration of toluene with nitric acid as nitrating agent in the presence of Cu 1Àx Co x Fe 2 O 4 (0 # x # 1) as nanocatalysts is described. The results of this protocol show that this nitration system can significantly improve the selectivity and the yield of 2,4-dinitrotoluene. The prepared spinel ferrites were characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FT-IR).Cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In NiF and CuF photocatalysts, Fe 2 O 3 was confirmed as an impurity that was absent in CoF and ZnF. The crystallite size of a ferrite nanoparticle was calculated using the Debye-Scherrer equation: D = 0.9λ/(β Cosθ), where D is the crystallite size, λ is the wavelength of Cu Kα radiation, β is the full width at half maximum of the diffraction peak, and θ is the Bragg angle 21 . The crystallite size for CoF, NiF, CuF, and ZnF was found to be 34 nm, 27 nm, 16 nm, and 36 nm, respectively (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In NiF and CuF photocatalysts, Fe 2 O 3 was confirmed as an impurity that was absent in CoF and ZnF. The crystallite size of a ferrite nanoparticle was calculated using the Debye-Scherrer equation: D = 0.9λ/(β Cosθ), where D is the crystallite size, λ is the wavelength of Cu Kα radiation, β is the full width at half maximum of the diffraction peak, and θ is the Bragg angle 21 . The crystallite size for CoF, NiF, CuF, and ZnF was found to be 34 nm, 27 nm, 16 nm, and 36 nm, respectively (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The high-intensity band in the range of 750-500 cm −1 (v 1 ) was attributed to the intrinsic stretching vibrations of the tetrahedral site-occupied metal-oxygen bond [M 2+ tetra ↔ O]. The low-intensity band 450-400 cm −1 (v 2 ) was due to the octahedral Fe 3+ -oxygen stretching vibration 21 . The broad band centered at 3427 cm −1 and a low-intensity band centered at 1630 cm −1 were assigned to the stretching and bending mode of O-H bonds of physically adsorbed water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…For spinel ferrites, the band appearing at the higher wave number (500-600 cm À1 ) is usually assigned to tetrahedral coordination while that at the lower wave number (385-450 cm À1 ) is oen ascribed to octahedral coordination. 46,47 Thus, it can be concluded that the products, S1P to S5P, correspond to the cobalt ferrite spinel. Avazpour et al 45 have obtained similar results with the absorption bands at 540 cm À1 and 331 cm À1 corresponding, respectively, to the tetrahedral and octahedral groups in cobalt ferrite.…”
Section: Resultsmentioning
confidence: 97%
“…The release profile of 9R from NPs was determined through a quantitative proton NMR experiment. 9R@ker was placed into dialysis bags, immersed in PBS at (i) pH = 7.4 (physiological conditions) and at (ii) pH = 5.5 in order to mimic the typical lysosomes acidic conditions (Figure C). ,, …”
Section: Resultsmentioning
confidence: 99%